Constructing Musicology - Williams, Alastair (Aldershot Ashgate, 2001)
There is widespread agreement that musicology has undergone a paradigm shift. This swing can be attributed to two not always separable causes: the wider repertoires now studied and the impact of theory on research in the humanities and social sciences. This analysis attends to both currents, examining and explaining the theoretical issues raised by various musics. Topics discussed include: Joseph Kerman's call for a shift from fact-finding to critical interpretation; Adorno's and Dahlhaus's scrutiny of the bourgeois tradition; the impact of post-structuralism on musicology; the semiotics of music; how gender is constructed in music; the relevance of psychoanalytical theory to musical understanding; classic critiques of the culture industry; how identity and image are negotiated in song; debates in ethnomusicology; and modernity in music. The author's overall aim is to show the forces at work in contemporary musicology, to demonstrate that traditions are socially constructed, and to suggest that established beliefs can be transformed in a theoretically flexible environment.